Pastoralism and resilience south of the Sahara - Little, Peter D.; McPeak, John G. (International Food Policy Research Institute, 2014)
The recent popularity of the term resilience in the development discourse concerning arid and semiarid lands in Africa can be traced to two major international issues. The first is climate change, concerned with how to build resilient communities in the face of increasingly extreme weather events. The other is recurrent humanitarian crises, especially traced to the most recent drought‐ and conflict‐induced 2011 disaster in the Horn of Africa.